PENGARUH MOTIVASI KERJA DAN BUDAYA ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) KARYAWAN PADA PT BANK SYARIAH INDONESIA, TBK KANTOR CABANG BATURAJA - Dewi, Rosmala; Priharti, Rr. Dimas Veronica; Suroso, Suroso (STIE DWI SAKTI BATURAJA, 2024)
This research aimed to determine the influence of work motivation and organizational culture on employees'organizational citizenship behavior at PT. Bank Syariah Indonesia, Tbk Baturaja Branch Office. The datacollection technique used in this research was through distributing questionnaires. The total population was37 people. The data analysis technique used was Multiple Linear Regression. Based on the partial analysisresults, there was a positive influence of work motivation on organizational citizenship behavior with acalculated t value of 13,319. The organizational culture variable had a positive influence on organizationalcitizenship behavior with a calculated t value of 7.515. Simultaneously, it was found that there was aninfluence of work motivation and organizational culture on organizational citizenship behavior at PT BankSyariah Indonesia, Tbk Baturaja Branch Office. The coefficient of determination (R2) obtained was 0.994. Thisshowed that the contribution of work motivation and organizational culture to organizational citizenshipbehavior was 99.4%, while the remaining 6% was influenced by other variables outside this research, namelyjob satisfaction, personality, employee morale, leadership style, and trust in leaders (Titisari, 20144: 15)Keywords: Work Motivation, Organizational Culture and Organizational Citizenship Behavior